2020
DOI: 10.1016/j.bbr.2019.112256
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a robotic predator as a stimulus in conditioned place aversion for the study of the effect of ethanol and citalopram in zebrafish

Abstract: Zebrafish are becoming a species of choice in psychopharmacology, laying a promising path to refined pharmacological manipulations and high-throughput behavioral phenotyping. The field of robotics has the potential to accelerate progress along this path, by offering unprecedented means for the design and development of accurate and reliable experimental stimuli. In this work, we demonstrate, for the first time, the integration of robotic predators in place conditioning experiments. We hypothesized zebrafish to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Moreover, the robots are also used as demonstrators in social learning experiments [39]. Moreover, some animals resulted to have similar features in different neural circuit organization, making them valuable models to test neurological diseases in humans [40], [41], [42]. However, these therapies do not focus on checking the effectiveness of different types of stimuli that can be generated by a robot during the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the robots are also used as demonstrators in social learning experiments [39]. Moreover, some animals resulted to have similar features in different neural circuit organization, making them valuable models to test neurological diseases in humans [40], [41], [42]. However, these therapies do not focus on checking the effectiveness of different types of stimuli that can be generated by a robot during the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Geotaxis is considered a very sensitive behavioral indicator of anxiety-related states (Kalueff et al, 2013 ). It has been validated in a wide range of experimental paradigms (Clèment et al, 2020 ; Karakaya et al, 2021 ), and it has been repeatedly reported to vary as a function of the administration of selective serotonin reuptake inhibitors like Citalopram (Wong et al, 2010 ; Cachat et al, 2011 ; Kalueff et al, 2016 ; Collier et al, 2017 ; Macrì et al, 2019 ). To further delve into the nature of shoaling and schooling tendencies, we conducted a thorough analysis of polarization (Aureli et al, 2012 ) and neighbor distances (Rosa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tank width and depth were selected to promote swimming along the water column. Such decision rested upon the hypothesis that SSRIs generally result in an overt alteration of geotaxis (Sackerman et al, 2010 ; Macrì et al, 2019 ; Clèment et al, 2020 ); this strategy has been borrowed from available literature (Cachat et al, 2011 ; Mathuru et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations